Genome-wide association and replication study of anti-tuberculosis drugs-induced liver toxicity. (December 2016) - Petros, Zelalem; Lee, Ming-Ta; Takahashi, Atsushi; Zhang, Yanfei; Yimer, Getnet; Habtewold, Abiy; Amogne, Wondwossen; Aderaye, Getachew; Schuppe-Koistinen, Ina; Mushiroda, Taisei; Makonnen, Eyasu; Kubo, Michiaki; et al.
Abstract Background Drug-induced liver injury (DILI) is a well-recognized adverse event of anti tuberculosis drugs (ATD) possibly associated with genetic variations. The objective of this study was to perform genome-wide association study (GWAS) to identify genetic variants associated with the risk for ATD induced liver toxicity in Ethiopian patients. Result Treatment-naïve newly diagnosed tuberculosis patients (n = 646) were enrolled prospectively and treated with rifampicin based short course anti-tuberculosis therapy. Whole genome genotyping was done using Illumina Omni Express Exome Bead Chip genotyping array with 951, 117 single nucleotide polymorphisms (SNPs) on 48 DILI cases and 354 ATD tolerants. Replication study was carried out for 50 SNPs with the lowestP -values (top SNPs) using an independent cohort consisting of 27 DILI cases and 217 ATD tolerants. In the combined analysis, the top SNP identified was rs10946737 (P = 4.4 × 10−6, OR = 3.4, 95 % confidence interval = 2.2–5.3) in the intron ofFAM65B in chromosome 6. In addition, we identified a cluster of SNPs with suggestive genome-wide significance in the intron of ATP/GTP binding protein-like 4 (AGBL4 ). Conclusion We identified genetic variants that are potentially associated with ATD induced liver toxicity. Further studies with larger sample sizes are essential to confirm the findings.